Genomic Stability of Composite SCCmec ACME and COMER-Like Genetic Elements in Staphylococcus epidermidis Correlates With Rate of Excision - Almebairik, Nada; Zamudio, Roxana; Ironside, Corinne; Joshi, Chaitanya; Ralph, Joseph D.; Roberts, Adam P.; Gould, Ian M.; Morrissey, Julie A.; Hijazi, Karolin; Oggioni, Marco R. (Frontiers in Microbiology, 2020)
The epidemiological success of methicillin-resistant Staphylococcus aureus USA300 has been associated with the presence of two mobile elements, the arginine catabolic mobile element (ACME) and the copper and mercury resistance (COMER) element. These two mobile elements are associated with resistance to copper, which has been related to host fitness and survival within macrophages. Several studies found that ACME is more prevalent, and exhibits greater diversity, in Staphylococcus epidermidis while COMER has not been identified in S. epidermidis or any other staphylococcal species. We aimed in this study to evaluate the presence and diversity of ACME and COMER-like elements in our S. epidermidis clinical isolates. The genomes of 58 S. epidermidis clinical isolates, collected between 2009 and 2018 in a Scottish hospital, were sequenced. A core-genome phylogenetic tree and genome based MLST typing showed that more than half of the isolates belong to the clinically predominant sequence type2 (ST2) and these isolates have been found to split into two lineages within the phylogenetic tree. Analysis showed the presence of SCCmec in the majority of isolates. Comparative analysis identified a cluster of ACME-positive isolates with most of them belonging to ST48. ACME showed high variation even between isolates of the same ACME type and ST. COMER-like elements have been identified in one of the two major hospital adapted drug resistant ST2 lineages; and showed high stability. This difference in stability at the genomic level correlates well with the up to one hundred times higher excision frequency found for the SCCmec elements in ACME-containing isolates compared to COMER-like element containing isolates. ACME / COMER-like element positive isolates did not show a significant phenotype of decreased copper susceptibility, while resistance to mercury was over-represented in COMER-like element positive isolates. To the best of our knowledge, this is the first molecular characterization of COMER-like elements in S. epidermidis isolates. The presence of the COMER-like elements is the most prominent accessory genome feature of these successful lineages suggesting that this chromosomal island contributes to the success and wide clinical distribution of ST2 S. epidermidis.